2020
DOI: 10.1038/s42003-020-1088-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in SARS-CoV-2 infection rates and the potential link to prostate cancer

Abstract: The recent outbreak of infections and the pandemic caused by SARS-CoV-2 represent one of the most severe threats to human health in more than a century. Emerging data from the United States and elsewhere suggest that the disease is more severe in men. Knowledge gained, and lessons learned, from studies of the biological interactions and molecular links that may explain the reasons for the greater severity of disease in men, and specifically in the age group at risk for prostate cancer, will lead to better mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(163 citation statements)
references
References 144 publications
(123 reference statements)
4
155
1
3
Order By: Relevance
“…Several unique mutations in NSP3 followed by S, ORF3a, NSP2, RdRp, helicase, E and N protein were observed in this study, which may contribute to virulence, transmission, and pathogenicity during the epidemic (Consortium et al, 2004). Interestingly, accumulating mutations were found to be higher in males than female patients, which was also reported from other countries including Italy showing male to female ratio being 3:1 in Italy (Chakravarty et al, 2020). The mortality rate was also reported high in males compared to females from China showing 2.4 times higher mortality in males (Jian-Min et al, 2020), New York State of USA (42% females vs. 58% males (https://www.syracuse.com/coronavirus-ny/).…”
Section: Discussionsupporting
confidence: 79%
“…Several unique mutations in NSP3 followed by S, ORF3a, NSP2, RdRp, helicase, E and N protein were observed in this study, which may contribute to virulence, transmission, and pathogenicity during the epidemic (Consortium et al, 2004). Interestingly, accumulating mutations were found to be higher in males than female patients, which was also reported from other countries including Italy showing male to female ratio being 3:1 in Italy (Chakravarty et al, 2020). The mortality rate was also reported high in males compared to females from China showing 2.4 times higher mortality in males (Jian-Min et al, 2020), New York State of USA (42% females vs. 58% males (https://www.syracuse.com/coronavirus-ny/).…”
Section: Discussionsupporting
confidence: 79%
“…In stage 1, the virus binds to the angiotensin-converting enzyme 2 (ACE2) receptor, a transmembrane protease, serine 2 (TMPRSS2). TMPRSS2 is ubiquitous in the human body; it is found in the nasal cavity and lung and is also expressed throughout the intestine and prostate [ 14 ]. ACE2 receptors can also be found in the heart, esophagus, kidneys, stomach, bladder, and ileum [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…TMPRSS2 is ubiquitous in the human body; it is found in the nasal cavity and lung and is also expressed throughout the intestine and prostate [ 14 ]. ACE2 receptors can also be found in the heart, esophagus, kidneys, stomach, bladder, and ileum [ 12 , 14 ]. As SARS-CoV-2 progresses down the respiratory tract, the virus begins to activate a more potent immune response and certain patients may manifest clinically with respiratory failure and ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…Males tend to have higher severity and mortality in COVID-19 than female [26]. Although the exact cause of high mortality and severity in male has not been clari ed, previous research using mouse model of viral pneumonia suggested that estrogen might suppress excessive immune responses to virus infection in lung [27].…”
Section: Discussionmentioning
confidence: 99%